Computational Analysis of Bifurcation of Raghuganga Hydropower Project - Dhakal, Rajendra; Shrestha, Rajendra (Journal of Advanced College of Engineering and Management, 2023)
Computational analysis is the modern design optimization tool used widely for determining the effect of different loading parameters where operating conditions and geometry are complex for manual solutions to execute. This study has great significance in the design and optimization of penstock branches as the ancient technology used for the design has least chance of having minimum head loss and good structural strength at the same time. Bifurcation of Raghuganga Hydropower Project of 40 MW installed capacity is chosen for this study in which, head loss, velocity and pressure distribution and stress distribution around the branching regions have been observed by varying the angle of cone of bifurcation. Upon varying the cone angles gradually starting from 3 degrees up to 15 degrees, the values of head loss have been reduced from 0.972 m to 0.086 m till 13-degree angle of cone and upon further increasing the angle to 15 degrees, the head loss increased sharply to 2.201 m. Also, for the structural analysis on the optimized cone angle profile, pipe thickness was varied from 25 mm till the values of stress was in the acceptable range. Upon simulations, it was found that optimum pipe thickness is 40 mm and sickle reinforcement of 75 mm with the value of maximum stress (Von-Mises) at the branching to be 167 MPa and minimum factor of safety of 1.49 for the material chosen i.e. E 250 corresponding to I S 2062.